GREEN SYNTHESIS OF NANOSTRUCTURED ZINC PARTICLES USING AQUEOUS LEAF EXTRACT OF SCHREBERA SWIETENIOIDES ROXB. AND THEIR CATALYTIC APPLICATION IN DEGRADATION OF METHYL ORANGE, CRYSTAL VIOLET DYES AND CHROMIUM METAL - TULASI, S. LAKSHMI; SWAMY, A. V. V. S.; PAVANI, P.; SUBHASHINI, V. (International Journal of Applied Pharmaceutics, 2022)
Objective: The present work was aimed to synthesized the zinc nanoparticles (ZnO NPs) using aqueous leaf extract of Schrebera swietenioides Roxb., and further, the green-synthesized ZnO NPs were studied for its efficacy in the degradation of hazardous dyes like methyl orange, crystal violet and hazardous metal such as chromium. Methods: The ZnO NPs were synthesized using aqueous leaf extract of S. swietenioides Roxb., as a green reducing agent and 0.1 M Zinc acetate as metal source and the NPs synthesis was completed within a short period of 6 h. The ZnO NPs synthesized were characterized using SEM, TEM, EDS, XRD, FT-IR and UV-visible spectrophotometer. Further, the synthesized NPs were applied for reduction of pollutant days such as methyl orange, crystal violet and pollutant metal chromium. Results: The synthesis of NPs was monitored by observing the color change in the reaction mixture and UV visible spectral analysis. The UV spectral analysis shows a characteristic absorption wavelength at 379 nm. The synthesized NPs were hexagonal wurtzite form crystals having a spherical shape with rough surfaces with an average size of 68 nm and having 73.7 % of zinc content. At a NPs dose of 1.0 g/l the photocatalytic reduction was observed as 85.33±0.02 %, 86.82±0.095 % and 86.73±0.104 % for crystal violet dye, methyl orange dye and chromium metal, respectively. The NPs shows a high % photocatalytic reduction of chromium metal, crystal violet dye and methyl orange dye with less contact time confirms that the synthesized ZnO NPs were effectively catalyzed the degradation of methyl orange, crystal violet dyes and chromium metal. The NPs were observed to be recyclable and can shows high reduction activity after the completion of three cycles of degradation. Conclusion: Hence it can be concluded that synthesized greener nanocatalyst was efficient for pollutant treatment and demonstrated the power of green biosynthesis for metallic nanoparticles.